2014
DOI: 10.1021/ol502305j
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Triflate Catalyzed Tandem Reactions of d-Galactal: Toward Chiral Benzopyrans, Chromenes, and Chromans

Abstract: 3,4,6-Tri-O-acetyl-D-galactal is selectively converted into 1-O-aryl-2-deoxy derivatives or chiral bridged benzopyrans under Al(OTf)3 catalysis, depending on reaction conditions. The benzopyrans react with Al(OTf)3/acetic anhydride in ring-opening reactions in the absence or presence of acetic acid to selectively produce chiral chromenes or chromans, respectively, in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Importantly, it tolerates protic conditions and so can be readily recycled by simply extracting it in water and recovered by subsequent removal of the water. 52 A water-tolerant reusable Al(OTf) 3 Lewis acid catalyst for the propargylation of indoles 61 in reuxing acetonitrile was reported by Bezuidenhoudt and co-workers in the year 2012, Scheme 24. 53 From the environmental point of view, water-tolerant Lewis acids are quite attractive due to their recyclability and reusability attributes and the by-product from the reaction is also non-hazardous H 2 O.…”
Section: Aluminium Derived Catalystsmentioning
confidence: 99%
“…Importantly, it tolerates protic conditions and so can be readily recycled by simply extracting it in water and recovered by subsequent removal of the water. 52 A water-tolerant reusable Al(OTf) 3 Lewis acid catalyst for the propargylation of indoles 61 in reuxing acetonitrile was reported by Bezuidenhoudt and co-workers in the year 2012, Scheme 24. 53 From the environmental point of view, water-tolerant Lewis acids are quite attractive due to their recyclability and reusability attributes and the by-product from the reaction is also non-hazardous H 2 O.…”
Section: Aluminium Derived Catalystsmentioning
confidence: 99%
“…Signicant efforts have been made towards the synthesis of the 2H-chromene motif, 22 including sugar-derived chiral systems. 23 In addition, there has Scheme 2 Conversion of benzyl ethers into C-alkylated products. been continuing interest in heteroatom analogues of chromenes such as dihydroquinolines 24 and thiochromenes, 25 which are also associated with biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…Williams and Cullen reported that Al(OTf) 3 was an effective recyclable catalyst (<10 mol% catalyst loading) for the ring opening of epoxides with amines to provide β-amino alcohols without the catalyst being deactivated by the nucleophile amine or hydroxyl amine product. 36 Inspired by this result and in continuation of our research into the application of Al(OTf) 3 in a number of catalytic transformations such as in the synthesis of chiral O-heterocycles, 37 tetrahydropyranyl and tetrahydrofuranyl protection/deprotection of alcohols 38 and temperature-switched selective Oglycosylation, 39 we have evaluated its catalytic activity in the three component Povarov reaction and herein report its scope and limitations.…”
Section: Introductionmentioning
confidence: 94%